Cytotoxic, Antioxidant and Antimicrobial Effects of Root Bark Extracts of Gardenia angustifolia (Cape jasmine) - Sule Ajuma , Fatima; Omale, James; Olajide Eniola, Joseph (Iraqi Journal of Science, 2025)
Background: Empirical knowledge on the cautious application, safety and efficacy of medicinal plants is limited especially in developing countries around the world. Objective: This study is aimed at investigating the cytotoxic, antioxidant and antimicrobial potential of Gardenia angustifolia root bark with a comparative objective on ethyl acetate and methanol extracts. Methods: Compound elucidation was done using Gas Chromatography-Mass Spectrometry (GC-MS) analysis and Thin Layer Chromatography (TLC). Cytotoxic evaluation was conducted using Artemia salina and Human Embryonic Kidney-293 (HEK-293) cell line. Antioxidant assay was conducted using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Ferric Reducing Antioxidant Power (FRAP) models. The agar-well diffusion method was employed for antimicrobial assay. Results: Both crude extracts constitute thirty-five (35) bioactive components each by GC-MS analysis. The extracts showed a non-toxic effect toward brine-shrimp and HEK-293 cell line at a moderate concentration and displayed significant antimicrobial effects on some strains of microorganisms. Furthermore, the in vitro antioxidant analysis conducted using the DPPH and FRAP models revealed a concentration dependent antioxidant activity of the extracts. Conclusion: The findings indicate that ethyl acetate extract of Gardenia angustifolia root bark is a better radical and microbial growth inhibitor, attesting to its antioxidant nature and as a promising target in antimicrobial drug design.